LEGAL NORMS WITH IMMEDIATE EFFECT: UNDERSTANDING AND ADMISSIBILITY IN THE STATE OF LAW - Maris Onzevs (European Scientific Journal, ESJ, 2013)
The article analyses the understanding on the rights of a legislator to pass legal norms with immediate effect. Although, up to now legal doctrine has viewed inadmissibility of retroactive legal norms more largely, in practice there are a lot more legal norms with immediate effect passed. Therefore the article firstly assesses features according to which legal norms related to past are passed with an immediate effect. Similarly, in light of the general view of case-law and legal doctrine that prima facie consider legal norms with immediate effect admissible and lawful, the article reveals the historical origin and development of this opinion. In addition, as the above assumption on admissibility of the legal norms with immediate effect is not absolute and is exposed to assessment of legitimate expectations of addressees of legal norms, a significant attention has been drawn to methodology of the admissibility assessment. Within the framework of analysis of methodology, the article views both different methods applicable for assessment of public interest and addressees of legal norms in cases of immediate effect as well as various circumstances that might be the basis to acknowledge legal norms with immediate effect as illegitimate.